Analisis Penjualan Polis Asuransi Jiwa dan Pengelolaan Nilai Investasi Nasabah Pada Asuransi Jiwa Manulife Cabang Batam - Mhd Yudha Pratama; Diamon Sembiring (Jurnal Akuntansi, Manajemen dan Ekonomi Digital, 2021)
Abstract − To develop one's own funds, one needs to invest in order to get a higher return in the future. Because of this opportunity, insurance companies began to issue insurance products combined with investment. The type of research used is descriptive qualitative research. Data collection techniques are interviews with the parties concerned and literature review. The results of the analysis show that the company has made efforts so that customers can easily buy life insurance and see or review the development of investments in the market by making reports on a daily basis and can be accessed through the company's website or print media.Keywords: Sales Analysis, Manager Performance, Investment Management